UPAYA MENIGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIKA SISWA MELALUI PENDEKATAN OPENENDED - marliana marliana (Universitas Asahan, 2019)
AbstractThis study aims at determining the effort ti improve students’ mathematical eritical thinking ability through an Open-Ended Approach in algebraic material at class VII-1 of MTs.PP Daarul Hikmah Sei Alim Hassak in the academic year of 2018/2019. The subject in this study was class VII-1 MTs.PP Daarul Hikmah Sei Alim Hassak, amounting to 40 people. The object of this research was the students’ mathematical critical thinking ability in algebraic material at class VII-1 of MTs.PP Daarul Hikmah Sei Alim Hassak in the academic year of 2018/2019. This type of research was PTK. Data needed in this study was obtained from test and observation. The test used was a description test the was given to sstudents after learning through the Open-Ended Approach. Before the test was carried out, the questions were first tested outside the sample to determine the validity and reliability. Data analysis used in this study were: level of students’ mastery on subject matter and observation result. From the results of the data analysis above, it can be concluded that the application of learning through an Open-Ended Approach is affectively used on the subject of algebraKeywords:Critical Thinking Ability, Open-Ended Approach, Algebra